Research advances in low-concentration rare earth ion adsorption materials - Xuyi WEI; Junwei HAN; Wenqing QIN (工程科学学报, 2024)
Recently, with the persistently increasing demand and production of rare earth metals, the efficient and green recovery of rare earth resources has encouraged higher requirements. Particularly, the recovery of rare earth elements (REEs) from low-concentration rare earth solutions such as rare earth mineral processing wastewater, refining wastewater, seawater, and hot springs has become a research hotspot. Compared with conventional extraction methods, such as evaporative crystallization, chemical precipitation, and solvent extraction, adsorption holds promise for low-concentration rare earth recovery due to its advantages of simple operation, low cost, large treatment capacity, and strong adaptability. This paper meticulously outlines the recent research advancements on rare earth ion adsorption materials and introduces mineral-based, carbon-based, metal–organic framework (MOF)-based, and polymer-based adsorbents and their design ideas, microscopic morphologies (specific surface area, pore size, and particle geometric dimension), adsorption behaviors (adsorption kinetics and adsorption isotherm), material performances (maximum adsorption capacity, adsorption–desorption cycles, and stability), and potential applications (pH, dosage, coexisting competing ions, and actual REE wastewater treatment effect). Mineral-based adsorbent materials are characterized by clay minerals of layered silicate type; carbon-based adsorbent materials include biochar, graphene, and carbon nanotubes; MOF materials include the Zeolitic imidazolate framework (ZIF), University of Oslo (UIO), Materials of Institut Lavoisier (MIL), and Hong Kong University of Science and Technology (HKUST) series; polymer-based materials include natural and artificial polymers and hydrogels. Single-material adsorbents usually have low adsorption capacity, poor selectivity, and weak mechanical strength and are unstable under acidic conditions. To overcome these disadvantages, composite materials can be prepared, which capitalize on the benefits of their individual materials, e.g., use of polymer hydrogels loaded with fine-grained mineral materials to prevent agglomeration, in-situ MOF growth on the surface of graphene oxide to improve its stability in acidic conditions, use of polymers with specific functional groups that contain O, N, and P to alter porous materials to improve adsorption capacity, and magnetization modification of carbon-based materials and polymers to facilitate the subsequent recycling. Finally, the following future development trends of rare earth adsorbents are proposed: 1) development of green adsorbent materials, including green raw materials and no new pollution in the process, 2) development of highly selective adsorbent materials that can extract REEs from competing impurity ions and achieve the separation of a single rare earth among the REEs, and 3) development of high-efficiency adsorbent materials including REE extraction from low-concentration rare earth solutions and fast adsorption kinetics and their applications in the field of REE wastewater treatment.